Eigendecomposition-based pose detection in the presence of occlusion - Roberts, Rodney G., author; Balakrishnan, Venkataramanan, author; Maciejewski, Anthony A., author; Chang, Chu-Yin, author; IEEE, publisher (Colorado State University. Libraries, 2001)
Eigendecomposition-based techniques are popular for a number of computer vision problems, e.g., object and pose detection, because they are purely appearance-based and they require few on-line computations. Unfortunately, they also typically require an unobstructed view of the object whose pose is being detected. The presence of occlusion precludes the use of the normalizations that are typically applied and significantly alters the appearance of the object under detection. This work presents an algorithm that is based on applying eigendecomposition to a quadtree representation of the image dataset used to describe the appearance of an object. This allows decisions concerning the pose of an object to be based on only those portions of the image in which the algorithm has determined that the object is not occluded. The accuracy and computational efficiency of the proposed approach is evaluated on sixteen different objects with up to 50% of the object being occluded.
Keywords: eigenvalues and eigenfunctions; computer vision; computational complexity; object detection; quadtrees